Inverted Y ureter anomaly and associated distal yo-yo phenomenon - (:unkn) unknown (Blackwell Publishing, 1998)
Duplication of the distal ureter is a very rare anomaly. A case is reported here in which the lower ectopic limb of the duplicated distal ureter presents with a ureterocele, and shows a different pattern of backflow.
Keywords: Inverted Y ureter; Ureter duplication